2011
DOI: 10.1177/0003319710387918
|View full text |Cite
|
Sign up to set email alerts
|

Early Identification of Vascular Damage in Patients With Systemic Sclerosis

Abstract: Vascular involvement in systemic sclerosis (SSc) plays a key role in the pathogenesis of fibrosis. We assessed arterial stiffness using a new echo-tracking technique in patients with SSc asymptomatic for cardiovascular diseases. We enrolled 22 patients (21 female, 63 ± 14 years) and 20 controls (12 female, 62 ± 3 years). Carotid intima-media thickness (IMT) was comparable between the 2 groups (1.1 ± 0.3 vs 1.0 ± 0.4 mm, P = ns), whereas the stiffness parameters were significantly increased in patients (β: 9.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
(31 reference statements)
1
7
0
2
Order By: Relevance
“…20 Previous studies have demonstrated possible clinical applications of this software, highlighting the feasibility of vascular function assessment in different clinical conditions. 38,[46][47][48] Our results confirm those from other studies that used the same system and showed an inverse relationship between diastolic function and echo-tracking parameters (elastic modulus, b stiffness and PWV) in diabetes patients, normal individuals and patients with different diseases. 49,50 Limitations Study population size was relatively small, particularly the subgroup with grade I diastolic dysfunction; this impairs the capacity to generalize our findings.…”
Section: Discussionsupporting
confidence: 88%
“…20 Previous studies have demonstrated possible clinical applications of this software, highlighting the feasibility of vascular function assessment in different clinical conditions. 38,[46][47][48] Our results confirm those from other studies that used the same system and showed an inverse relationship between diastolic function and echo-tracking parameters (elastic modulus, b stiffness and PWV) in diabetes patients, normal individuals and patients with different diseases. 49,50 Limitations Study population size was relatively small, particularly the subgroup with grade I diastolic dysfunction; this impairs the capacity to generalize our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Systemic sclerosis (SSc) is an autoimmune disease characterized by inflammation, widespread vascular lesions and fibrosis involving various tissues and organs such as skin, lungs, gastrointestinal tract, kidneys, heart and blood vessels [1-3]. Multiple cardiac abnormalities, including ventricular arrhythmias, conduction disturbances, pericardial effusion, myocardial fibrosis and ischaemia, have been, frequently, reported in SSc and associated to a worse clinical course of the disease [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary arterial hypertension is a poor prognosis factor for SSC. In some studies, PWV was correlated with anti-Scl-70 antibodies and anticentromere antibodies [44]. Choi et al [45] showed that CCA-IMT was significantly thicker in SSC than in SLE after adjusting for risk factors.…”
Section: Augmentation Index and Markers Of Arterial Stiffness In Ctdsmentioning
confidence: 99%